EFEKTIVITAS TERAPI BODY SPACE MEDICINE DALAM MENANGANI NYERI PINGGANG KRONIS PADA PASIEN DI GEREJA KRISTEN PROTESTAN SIMALUNGUN (GKPS) PALEMBANG - Elmi Hayati; Hilman Rama Pratama (Bajang Institute, 2025)
Elmi Hayati / 20230302790548 / 2025 / The Effectiveness of Body Space Medicine Therapy in Managing Chronic Low Back Pain in Patients at the Simalungun Protestant Christian Church / Ir. Hilman Rama Pratama, S.Ud., S.Tr.Kes., M.Pd. Chronic low back pain is a musculoskeletal disorder that often reduces quality of life and productivity. In the ICD-11, Chapter 26 Traditional Medicine (TM1), chronic low back pain is categorized as Lumbago or Yao Tong (腰痛) with the code SC61 Yao Tong. Body Space Medicine (BSM) or Kōngjiān Yīxué is a modern therapeutic method rooted in Traditional Chinese Medicine (TCM) philosophy, emphasizing the balance of body energy through the harmonization of internal spaces. This study aims to determine the effectiveness of BSM therapy in patients with chronic low back pain at GKPS Palembang. The research employed a case study design involving three patients who underwent six sessions of BSM therapy. Evaluations were carried out through anamnesis, tongue observation, vital sign assessment, and patients’ subjective responses. The results showed a decrease in pain intensity, improvement in sleep quality, increased vitality, and positive changes in tongue condition. In conclusion, BSM therapy is effective as a complementary approach to reduce chronic low back pain complaints and improve quality of life.